Quest for the Aesthetics of Sustainability and Sustainable Architecture in the Digital Age - Khetani, Katalin Puskas (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Architectural styles or architectural aesthetics are very powerful tools for expressing the very core values, customs, emotions, thoughts and philosophies of a culture or society. The emergence of each architectural style was a result of a great shift in humanity’s way of life. The reviewed literature suggests that these major shifts in the history of man were caused by technical development and innovations of industrial revolutions. These new incremental technological changes created a human development path that reached a level which is no longer sustainable. Sustainability became possibly the most important motto of our age however, the pronounced sustainable architectural style and aesthetics that would communicate the underpinning philosophies, thoughts, emotions and values is yet to emerge. This article aims to investigate the underlying conditions and factors why sustainability has not yet revealed itself aesthetically as a distinctive architectural style.